The Analysis of The Mathematical Problem-Solving Ability of High School Students Reviewed from Personality Types of The Rational and Artisan. (February 2019) - Putra, R W Y; Supriadi, N; Ilmiyana, M; Khoiriah; Fitriani, D; Aziz, A F; Solihat, T
Abstract: The aim of this study is to determine how to analyze the mathematical problem-solving ability of high School students reviewed from personality types of the Rational and Artisan. This research is a descriptive qualitative. The subject of this study consists of 2 students of class X in the city of Liwa, Lampung Barat. Retrieval of the subject using the purposive sampling, ie sampling technique with certain considerations. The stages used is the stage proposed by Polya. Data collection techniques were triangulation techniques by comparing the results of test problem-solving ability and results of the interview. The results of the discussion can be concluded that the analysis of students' problem-solving abilities type of personality rational is better in comparison with the type of personality of the artisan. Because this type can already be passed through all stages, from understanding the problem, planning, finish planning, and looking back the answer with good, personality types this tend to be quick and can apply ideas in solving a problem, while the students with the type of personality of the Artisan have not passed all indicators, students do not write down information on the matter and don't look back the answer, problem-solving abilities with personality type artisan too rushed and less thorough in doing a matter, so at the stage of completing the plan answers less than the maximum.